Describing paediatric burn injuries at an academic hospital in Blantyre, Malawi - Mzama, Idah (My University, 2016)
Introduction and back ground Burn injuries in children remain one of the leading causes of deaths and disabilities worldwide. It is estimated that 5 million children die from burn injuries every year. In Malawi burn injuries are reported to be the third leading cause of deaths in children. No known study has been conducted at Queen Elizabeth Central Hospital (QECH) Burns Unit to describe the characteristics of children with burn injuries and their outcomes. However, an observation study was conducted previously that looked only at the aetiology, presentation and management of all the burn injuries that were being attended to at QECH. On the other hand, the current descriptive, retrospective, quantitative study aimed at describing the characteristics of the paediatric burn injuries at an academic hospital in Blantyre, Malawi. Methodology The study used descriptive, retrospective design that employed quantitative data collection and analysis methods. The study reviewed 148 patients’ files of paediatrics with burn injuries admitted during the period from September 2011 to August 2012 at the Burns Unit of QECH in Malawi. The study used a checklist to extract information on demographics, causes, anatomical distribution, depth, place of incidence of the burn injury, period taken from time of incidence to time of arrival to hospital, season of the year when the incidence occurred, whether the child had been admitted straight to QECH or referred, complications that occurred, period of hospitalisation and outcomes. Data was analysed using Microsoft Excel 2007® (Microsoft, Seattle, USA). For the purpose of descriptive analysis, data was then exported to Statistical 9.1® (Stat soft, Tulsa, USA) which was utilised for all other analysis. Results Results of the study showed that 51% (n=75) of the children admitted with burns over the period of the study were boys while 49% (n=73) were girls. Furthermore, males admitted with burn injuries were significantly younger than the females (p = 0.001 [Figure 2]). The median age for boys was 3 years (IQR: 2-4 years) whereas the median age for girls was 4 years (IQR: 2-6 years). Hot liquids and open fire were the only sources of burn injuries with hot liquids affecting 68% of children. The Arms and hands were the most affected body parts with about 59% while the least was the back. The depth of the burns were 17.2% (n=25) superficial, 52.7% (n=78) superficial partial, 7.5% (n=11) deep partial and 22.6% (n=34) full thickness burns. The incidents of burn injury that occurred in the home premises were 96.6% (n=143), 2% (n=3) at school and 1.4% (n=2) in the surrounding gardens. There were 42.5% (n=63) incidents of burn injuries that occurred in cool dry winter season, 43.8% (n=65) in warm wet and 13.7% (n=20) in hot dry season. The outcome of the burn injuries were that the median length of hospitalisation was 14 days (IQR: 7-27).The children who were discharged were 75.7% (n=112) and had median of 16 days (IQR: 11-29 days) in hospital. The children who died were 24.3% (n=36) and had median of hospital stay of 5 days (IQR: 3-10 days). Children who died spent significantly less number of days in hospital than those that were discharged. Out of 148 children, 59 were referred from other health centres to QECH representing 40%. Children that were admitted directly to QECH were associated with a 57% decreased odds of mortality compared to those referred from other health facilities OR 0.43 (95% CI: 0.20-0.93). Conclusion The study concluded that the male and female children were almost equally vulnerable to burn injuries. Hot liquids and open fire were found to be the only sources of burn injuries in this study. This was due to cooking places that were at ground level which were easily accessible by the children. Those that were referred from other health facilities were associated with 4 times odds of death from burn injuries compared to those that were admitted straight to Queen Elizabeth Central Hospital (OR 3.79 (95% CI: 1.33-10.79), p<0.001. Based on the results, it could also be concluded that burn injuries in children mostly affected the under five year children. The mortality was greatly influenced by the referral systems, total burnt surface area (TBSA), depth of the burns, and age of the child. Results of the study have implications on improving the referral system and community sensitisation on the prevention of burns.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfillment of the requirements for the Degree of Master of Science in Medicine Child Health Community Pediatric